The Contribution of Ultrasound in Exploring Women Pelvic Pathologies in Two Teaching University Hospitals Maternities in Cotonou - YEKPE ÉPSE AHOUANSOU, HERMIONE PATRICIA FRIDA; ADJADOHOUN, S; M. SAKA; G. NGAMO; SANSOUAMOU, T; SAVI DE TOVE, KOFFI MENSA; OLIVIER, BIAOU; VICENTIA, BOCO (My University, 2020)
Objective: The aim of this piece of work is to study the contribution of pelvic ultrasound while exploring pelvic pathologies at Hubert Koutoukou Maga Teaching University Hospital “CNHU-HKM” and at the Teaching University Hospital of Mother and Child “CHU-MEL” of Cotonou. Patients and Methods: A descriptive, cross-sectional and analytical study with prospective collection was carried out at the University Clinic of Gynecology and Obstetrics “CUGO” at the CNHU-HKM and in the gynecology department of the CHU-MEL, over a period of 4 months (May to August 2018). We included in this study women over 12 years old who performed a pelvic ultrasound and were followed in the aforementioned health centers. Results: The population of the study consisted of 181 patients. The pelvic ultrasound request frequency was 18.84% compared to all ultrasound examinations. The age group of 25 - 29 years old was the most represented (22.10%). Pelvic pain was the first motive for pelvic ultrasound request (39.8%). The abnormalities found by ultrasound were uterine and ovarian respectively in 55.4% and 38% of cases. Uterine pathology was dominated by uterine myoma (44%). Ovarian cyst (13%) and ovarian dystrophy (14%) were the main ovarian pathologies. There was a statistically significant relationship between certain reasons for consultation, mainly metrorrhagia, dysmenorrhoea, amenorrhoea, leucorrhoea (p < 5%) and the ultrasound result. Conclusion: The ultrasound remains the first choice examination and is of a great value in exploring pelvic pathologies. In most cases, it helps to find the responsible lesion and to make the appropriate therapeutic decisions.
Keywords: Ultrasound; Pelvis; Woman; Cotonou